Tradisi VS Modernitas: Konflik Generasi dan Komunikasi Gender dalam Crashing Eid - Lilis Widarti; Rifma Ghulam Dzaljad; Yulia Rahmawati (Da'watuna: Journal of Communication and Islamic Broadcasting, 2024)
This study investigates the intricate dynamics of tradition versus modernity through the lens of generational conflict and gender communication in the Netflix series "Crashing Eid." Utilizing a systematic content analysis, the research aims to identify and categorize representations of these themes within the series. The analysis focuses on key aspects such as traditional versus modern values, generational perspectives, and gender roles as depicted in the interactions and dialogues of the characters. The findings reveal that "Crashing Eid" effectively portrays the tension between traditional and modern values, particularly in the context of family expectations and personal aspirations. The series highlights the challenges faced by younger generations in balancing respect for cultural heritage with the desire for individual autonomy. Gender communication is intricately woven into these narratives, showcasing the evolving roles of women and men within the Saudi Arabian cultural setting. The study underscores the importance of media representation in reflecting and shaping societal norms and values. "Crashing Eid" serves as a poignant example of how contemporary media can address and bring to light the complexities of generational and gender-related conflicts. The research contributes to the broader discourse on cultural change and continuity, emphasizing the role of media in facilitating dialogue and understanding across different societal segments.